THE SOCIAL ABYSS IN TIMES OF PANDEMICS: : IS EDUCATION A RIGHT FOR ALL OR A PRIVILEGE? - Sousa Costa, Wanderson; de Sousa Costa, Raquel (Revista Gênero e Interdisciplinaridade, 2022)
Since the advent of the pandemic caused by SARS-CoV-2 (known as COVID-19), the world has had to adapt abruptly to new forms of behavior and organization, with educational models being one of the most affected by numerous protocols, decrees and health measures aimed at reducing the number of people affected by the disease. In this context, we seek, through theoretical and methodological debate, to discuss access to the educational system in the context of teaching in times of pandemic, understanding that this is an adverse reality. During the debate, it is evident how the poor distribution of income, the lack of public policies aimed at the context of the pandemic, and the lack of concern of government agencies in democratizing access to technology and communication mechanisms between students and schools are factors responsible for the abyss that pervades the Brazilian educational system. But in addition, discuss the role of School Management in the pandemic context as well as the challenges, strategies and established goals.